Perceived parental alcohol problems and drinking patterns among adolescents in Sweden - Hiwot Mezgebe Workie; Joakim Wahlström; Johan Svensson; Sara Brolin Låftman (Addictive Behaviors Reports, 2024)
Introduction: Much research into the links between parental problematic alcohol use and adolescent substance use has focused on clinically diagnosed parental alcohol disorders. Few prior studies have utilised validated measures of adolescents’ perception of parental alcohol problems and considered the severity of these problems. This study examined the associations between the severity of perceived parental alcohol problems and adolescents’ drinking patterns in a Swedish national sample. Methods: We used survey information from grade 9 and 11 students (15–18 years) from 2021 (n = 9,227). Perceived parental alcohol problems were measured by the short version of The Children of Alcoholics Screening Test (CAST-6). The outcomes were: alcohol consumption during the past 12 months, frequent heavy episodic drinking (HED), and early alcohol debut (before age 14). Sociodemographic characteristics were adjusted for. Results: Binary logistic regressions showed that the severity of perceived parental alcohol problems was associated with alcohol consumption during the past 12 months (low severity OR 1.53, p < 0.001; moderate severity OR 1.85, p < 0.001; high severity OR 2.52, p < 0.001), HED (low severity OR 1.16, n.s.; moderate severity OR 1.31, n.s.; high severity OR 1.64, p < 0.01), and early alcohol debut (low severity OR 1.57, p < 0.001; moderate severity OR 1.65, p < 0.001; high severity OR 2.20, p < 0.001). Conclusions: Adolescents with perceived parental alcohol problems are more likely to have risky drinking patterns themselves, and the likelihood becomes higher with increased severity. Effective interventions for children whose parents have drinking problems are important, and should also take the severity of the parents’ drinking problem into account.